Pelatihan Tata Tulis Persuratan Tenaga Administrasi Sekolah di SMA Negeri 1 Sembawa, Banyuasin - Andriani, Margareta; Emawati, Emawati; Puspita Indah Sari, Ayu (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2024)
The development of the world of education requires that teachers and school administration staff are skilled at writing well and correctly. Correspondence writing is part of a series of writing activities and cannot be separated from a series of activities at school. To write and reply to incoming letters of course requires the competence of a school administration staff. In order to be professional, of course school administration staff must understand how to write letters well and correctly. This of course requires training in how to write good and correct correspondence, both in terms of effective sentence writing and good letter language. The theme of this training is how to write good and correct correspondence. This activity is expected to improve the understanding and skills of school officials, in this case administrative staff, in writing correspondence at school.